Molecular identification of Scopellaria marginata from East Java, Indonesia, based on trnL-UAA and trnL-trnF intergenic spacer regions - TURHADI, TURHADI; SUDARJAYANTI, BRILIYAN NATALINA; SOLIHAH, FIFI MAR’ATUN; AZRIANINGSIH, RODIYATI; AFIYANTI, MUFIDAH; ARUMINGTYAS, ESTRI LARAS (Nusantara Bioscience, 2024)
Abstract. Turhadi, Sudarjayanti BN, Solihah FM, Azrianingsih R, Afiyanti M, Arumingtyas EL. 2024. Molecular identification of Scopellaria marginata from East Java, Indonesia, based on trnL-UAA and trnL-trnF intergenic spacer regions. Nusantara Bioscience 16: 111-118. Scopellaria marginata (Blume) W.J.de Wilde & Duyfjes is a wild species in Cucurbitaceae, which was recorded as new expanding their distribution in East Java, Indonesia. The trnL-UAA and trnL-trnF intergenic spacer (IGS) sequences of Scopellaria are still limited in publicly accessible databases. This study aimed to evaluate the trnL-UAA and trnL-trnF IGS sequences of S. marginata from Malang, East Java. Total DNA of S. marginata was used to amplify the trnL-UAA and trnL-trnF IGS region. Then, the PCR products are sequenced using bi-directional Sanger dideoxy sequencing to obtain the DNA sequence of those two regions. The results showed that the partial sequences of S. marginata for trnL-UAA ranged from 528 to 571 bp, while the sequence for trnF-trnL IGS ranged from 434 to 445 bp. The S. marginata samples are similar to S. marginata in the database with similarity levels of 97.14-97.50% and 98.36-98.61%, respectively, based on the trnL-UAA and trnL-trnF IGS. Both trnL-UAA and trnL-trnF IGS showed a Correct Assignment Rate (CAR) of 100% for S. marginata. Two-dimensional DNA barcoding with lengths 505 and 417 bp for trnL-UAA and trnL-trnF IGS proposed as specific barcodes for S. marginata. These results prove that Malang, East Java was an additional distribution area for S. marginata in Indonesia.
Keywords: Cucurbitaceae, DNA barcoding, Scopellaria marginata, trnL-trnF intergenic spacer, trnL-UAA intron